Keong Darat Diplommatina spp (Moluska, Gastropoda) Di Taman Nasional Gunung Ciremai - Heryanto, Heryanto (Perhimpunan Biologi Indonesia, 2009)
ABSTRACTLand Snail Diplommatina spp (Mollusc, Gastropoda) at Ciremai Mountain National Park.The microscopies of land snail Diplommatinids depend on the water resources. This memberof mollusc can be used as a forest indicator. The results of the study shown that 50% JavanDiplommatinids found in this park. The study also indicated that Palatungan, Linggarjati andApuy (Argamukti) has Shannon and Weiner diversity: 1.33, 0.85, and 0.84, respectively.Key words: Diplommatina, Mollusc, TN. G. Ciremai